Revisiting Comparative Literature: Methodologies and Cross-Cultural Narratives - Dixit, Tanu (Journal of Advanced Research in English & Education; Vol 9 No 4 (2024): Journal of Advanced Research in English and Education, 2024)
Comparative literature, as an interdisciplinary field, offers a profound framework for analyzing literary texts across cultures, languages, and historical contexts. This review article revisits the methodologies employed in comparative literature, with a particular focus on how they facilitate the exploration of cross-cultural narratives. The paper critically examines the evolution of comparative literature as a discipline, discussing traditional and contemporary approaches to studying literary works from a comparative perspective. It highlights the ways in which comparative literature challenges monolithic understandings of culture and literature, emphasizing the dynamic exchange of ideas and influences between cultures. By tracing the development of key methodologies—from philological and historical approaches to postcolonial, feminist, and transnational frameworks—the article reveals how these perspectives contribute to broader global dialogues. Furthermore, the paper explores the importance of examining cross-cultural narratives that transcend national borders, acknowledging the fluid and interconnected nature of literary traditions. Through examining case studies and theoretical perspectives, the article also delves into how comparative literature can bridge gaps between national literatures, encourage intercultural dialogue, and contribute to global literary understanding, fostering empathy and shared human experience across different cultures. In considering the future of comparative literature, the article calls for further exploration of underrepresented voices and the impact of digital technologies, ensuring that the discipline remains adaptable, inclusive, and relevant in an increasingly interconnected world.